Atta sexdens (Hymenoptera: Formicidae) nests are located under higher canopy cover in colombian amazon rainforests - VAN-GILS, HEIKE A. J. A. (Revista Colombiana de Entomología, 2012)
Leafcutter ants, Atta and Acromyrmex spp., are dominant herbivores and important ecosystem engineers in the Neotropics. Some rainforest leafcutter ant species seem to be found in higher densities at forest edges or gaps, which in some cases are actively created by themselves. This implies the presence of a lower than average canopy cover which, in addition to several ant activities, may lead to vegetation diversification during and after colony life. This study compared canopy cover at active Atta sexdens nests and at random sites in three habitat types in the Colombian Amazon for the years 2008, 2006 and 1992. Canopy cover at nests and random sites was measured with a densiometer in 2008 and estimated by means of satellite images in 2006 and 1992. Contrary to expectation, canopy cover was found consistently higher at A. sexdens nests than at random sites. This and other nest aspects differentiate A. sexdens from other rainforest Atta species. Therefore, it is argued how A. sexdens is thought to affect rainforest vegetation differently as well.